METODE PENDIDIKAN KARAKTER DI PESANTREN - Fifi Nofiaturrahmah (Jurnal Pendidikan Agama Islam, 2014)
This article describes about the method of character education in pesantren. Character education in pesantren proved to be more effective than in schools or madrassas, because pesantren are able to develop students from various aspects, including intellectual ability, emotional and religious character formation, thus was born the output pesantren that have the knowledge and karimah morals or character. Success in shaping the character of boarding students because the student dormitory at boarding school education in guidance and supervision lodge chaplain, chaplain exemplary presence and authority as a religious leader in the school and the learning atmosphere at the school. In addition, the process of boarding school education place more emphasis on aqidah, worship and morals karimah with methods: exemplary, habituation, give advice, motivation, persuasion, story.